PENGARUH MATHEMATICAL HABITS OF MIND TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN DARING - Ani Suryani; Sukirwan Sukirwan; Etika Khaerunnisa (Penerbit Lafadz Jaya, 2023)
The lack of student understanding causes many students to have very low critical thinking skills, this is the background in this study. Therefore, students must be given various opportunities to develop mathematical critical thinking habits. Mathematical habits of mind can help students independently solve various problems in all aspects of life, from the very simple to the very complex. Mathematical habits of mind can help because they consist of various aspects, namely skills, attitudes, experiences, habits, and critical thinking. The type of research used is Ex-post facto or causal using a quantitative approach. While the research instruments used in this study are 2, namely non-tests, namely a mathematical habits of mind questionnaire consisting of 28 questions and tests, namely critical thinking ability test questions consisting of 4 description test questions. The objectives in this study are: (1) to find out whether students' mathematical habits of mind have a significant influence on their ability to think critically when learning online; and (2) to find out how much influence students' mathematical habits of mind have on their ability to think critically when learning online.